Armazenamento em atmosfera controlada dinâmica e destanização de caqui - Ludwig, Vagner (2022)
The main problem of persimmon storage is a high susceptibility to softening and skin browning after fruit removal from cool and transport during the shelf life. In Brazil, the main storage technique is the refrigerated atmosphere (RA), which allows storage for a maximum of 2 months and leads quality losses. Dynamic Controlled Atmosphere (DCA) is used due to reduced metabolism and better fruit conservation in apples. DCA can be a promising technique to reduce persimmon metabolism during storage and during shelf life. Temperature reduction, carbon dioxide partial pressure (pCO2) increases and 1-Methylciclopropene (1-MCP) are techniques that also reduce the fruit quality losses. The thesis is fortress in 3 chapters; [1] - The establishment of the minimum oxygen limit was evaluated using dynamic controlled atmosphere techniques monitored by the respiratory quotient (DCA - RQ 1.2) and anaerobic respiration point (DCA -ARP), the effect of 1-MCP application period on reduction of flesh firmness, softening and skin browning incidence, and overall quality of 'Fuyu' persimmon stored for 2 and 3 months. The low pO2 used in DCA methods retarded rapid softening and loss of pulp firmness after 2 and 3 months of storage plus 5 days of shelf life. The period of 1-MCP application is important when stored under DCA - ARP where the application after the storage period induced the highest amount of healthy fruit. Storage under DCA - ARP maintained the highest percentage of healthy fruits and flesh firmness, being a promising technique for the storage of 'Fuyu' persimmons for 2 or 3 months. [2] Establishment of ideal pCO2 for CA, DCA-PRA, DCA-QR1.2, and 0.4 kPa O2 (ULO) storage of 'Fuyu' persimmons, maintaining higher fruit quality. The pCO2 showed importance in the fruit stored under DCA and CA, being more indicated the use of 8 kPa due to the highest amount of healthy fruit. DCA-PRA, DCA- RQ 1.2 and ULO are alternatives for CA storage for 4 months, maintaining the quality of 'Fuyu' persimmon better than CA. DCA and ULO increase anaerobic metabolism compounds, mainly ethanol and acetaldehyde, but not to a high enough level to cause tissue damage, and they do not induce flesh firmness loss. The low pO2 confers better quality, leading to greater volatile organic compounds emission in relation to CA, mainly due to the anaerobic metabolism activation that induces higher concentrations of aldehydes and alcohols. [3] In addition, the response of anaerobic metabolism in reducing the astringency of persimmon cv. Rojo Brillante with the use of low pO2 was evaluated. The tannins removal from fruit with 0.5 kPa O2 + 1-MCP or 90 kPa CO2 + 1- MCP provided higher amount of healthy fruit, highest flesh firmness and lowest softening incidence. The tannins removal from the fruit without application of 1-MCP caused loss of flesh firmness and increase of softening incidence after 15, 30, and 45 days of storage under RA at 0.5 ºC plus 5 d at 20 ºC. The treatments to tannins remove caused a greater amount of acetaldehyde, ethanol and ethyl acetate, consequently they were efficient in the tannin removal. On the other hand, 0.5 kPa O2 + 1- MCP triggered an increase in several aldehydes and alcohols that play a relevant role of 'Rojo Brillante' persimmon aroma, being recommended for commercial use to provide persimmons with good quality and deastringency. After defining some parameters such as the ideal pCO2, application of 1-MCP time and finally the effectiveness of using DCA -PRA, it is possible to state that the new storage technology can be used for the storage of 'Fuyu' persimmon, having equal or better efficiency than storage in DCA- RQ or ULO with 0.4 kPa O2. Defining a sequence of efficiency in maintaining the quality of 'Fuyu' persimmons, it is possible to classify the storage techniques according to the following order: DCA -PRA> DCA -RQ or 0.4 kPa O2>CA.